Pengaruh Kepemilikan Institusional Dan Ukuran Dewan Terhadap Nilai Perusahaan Melalui Profitabilitas - Alda Nadya Mastuti; Dewi Prastiwi (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2021)
This research aimed to analyze and examine the effect of institutional ownership and board size on firm value with profitability as mediating variable. The dependen variables that used in this research are institutional ownership and board size, with firm value as independen variable and profitability as mediate variable.. Population that used in this research is consumer goods sector company sourced in secondary data that obtained through idx and company official website with 23 total sample obtained from purposive sampling. Data analysis technique used to examine the relationship between variables in this research is Path Analysis with IBM SPSS 24. The result show institutional ownership has negative effect on firm value, board size doesn’t effect firm value, profitability has not proved as mediate the effect of institusional ownership to firm value, profitability has not proved as mediate the effect of board size to firm value.